Pembelajaran Active Learning Tipe Picture and Picture dan Motivasi Berprestasi Terhadap Hasil Belajar Mata Pelajaran Sejarah pada Siswa - Beni Priyo Hutomo (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2019)
The value of IPS-Historical material under the KKM (> 75) is experienced by students of MAN 2 Pasuruan, especially Class XI. Based on the documentation study conducted by researchers, cases of low value of subjects occurred during the last 2 years period. The purpose of this study was to determine: (1) Significant Influence between Active Learning Type Picture and Picture Learning Results with Historical Subjects in Students, (2) Significant Influence between Achievement Motivation with Student Achievement Results in Historical History, and (3 ) Significant influence between Active Learning Type Picture and Picture Learning, Achievement Motivation with learning outcomes of Student History subjects. The research design used in this study was an experimental design. Research location in MAN 2 Pasuruan Pasuruan Regency. The study population was all students of Class XI = 204 students. While the sample was taken 50% = 102 students. Data collection by instrument / questionnaire. The instrument validity and reliability were tested. Data analysis using Anova. The results showed: (1) There was a significant influence between Active Learning Learning Picture and Picture Types with Learning Results of Historical Subjects in Class XI Students in MAN 2 Pasuruan Pasuruan Regency. Therefore, based on the calculation of the hypothesis test it appears that the calculated F value obtained was 45.310 with a significance of 0,000. Because of the significance <0.05, it can be concluded that there is a significant difference in the learning outcomes History after treatment between groups of students who learn with Active Learning learning models and groups of students who learn with Conventional learning models, (2) There is a significant influence between Motivation Achievers with the Learning Outcomes of History Subjects in Class XI MAN 2 Pasuruan, Pasuruan Regency. Based on the analysis of the second hypothesis test, it was seen that the calculated F value obtained was 12,080 with a significance of 0.001. Therefore the significance <0.05, it can be concluded that there are significant differences in the learning outcomes History after treatment between groups of students who have high achievement motivation and groups of students who have low achievement motivation, and (3) Significant influence between Active Learning Type Learning Picture and Picture, Achievement Motivation with student history learning outcomes. The analysis shows that there is no influence between active learning and achievement motivation. But partially there is an influence between learning with learning outcomes and there is an influence between learning motivation with learning outcomes.